Membrane Environment Enables Ultrafast Isomerization of Amphiphilic Azobenzene. Issue 8 (6th March 2020) - Paternò, Giuseppe Maria; Colombo, Elisabetta; Vurro, Vito; Lodola, Francesco; Cimò, Simone; Sesti, Valentina; Molotokaite, Egle; Bramini, Mattia; Ganzer, Lucia; Fazzi, Daniele; D'Andrea, Cosimo; Benfenati, Fabio; et al.
Abstract: The non‐covalent affinity of photoresponsive molecules to biotargets represents an attractive tool for achieving effective cell photo‐stimulation. Here, an amphiphilic azobenzene that preferentially dwells within the plasma membrane is studied. In particular, its isomerization dynamics in different media is investigated. It is found that in molecular aggregates formed in water, the isomerization reaction is hindered, while radiative deactivation is favored. However, once protected by a lipid shell, the photochromic molecule reacquires its ultrafast photoisomerization capacity. This behavior is explained considering collective excited states that may form in aggregates, locking the conformational dynamics and redistributing the oscillator strength. By applying the pump probe technique in different media, an isomerization time in the order of 10 ps is identified and the deactivation in the aggregate in water is also characterized. Finally, it is demonstrated that the reversible modulation of membrane potential of HEK293 cells via illumination with visible light can be indeed related to the recovered trans→cis photoreaction in lipid membrane. These data fully account for the recently reported experiments in neurons, showing that the amphiphilic azobenzenes, once partitioned in the cell membrane, are effective light actuators for the modification of the electrical state of the membrane. Abstract : The use of light to achieve control of cellular signaling is an important topic in pharmacology. Here, it is shown that an amphiphilic azobenzene performs ultrafast isomerization when partitioned into the cell membrane, while in water its photoisomerization ability is lost because of the formation of excimeric aggregates. This enables fast and reversible modulation of the membrane potential.